The suffering is expensive: comparison of therapeutic costs between palliative care and dysthanasia patient - de Freitas Melo, Cynthia; Vieira da Cunha, Dharana; Moreira Costa, Icaro; Huet Borges de Arruda, Gabriel; Feitosa Araújo, Danielle; Lins de Araújo Neto, João (Psicooncología, 2024)
Objectives: Several studies highlight benefits of palliative care for patients with lifethreatening illnesses, especially in terms of pain control and improving life quality. However, there is still research gap, particularly in the Brazilian context, regarding its ability to reduce costs associated with unnecessary invasive tests and procedures often invested in dysthanasia patients, thereby relieving the burden on the healthcare system. Given this scenario, the objective was to determine whether there is a significant difference in healthcare costs between cancer patients receiving palliative care and those in dysthanasia. Method: Documentary research, analyzing 94 medical records of patients who died from cancer in a hospital, divided into two groups: 47 in palliative care and 47 in dysthanasia. The groups had their average costs compared by surveying all tests and procedures recorded in the last 30 days of each patient’s life, with values scored based on the price table of the Unified Health System (Sistema Único de Saúde). Results: Patients receiving curative care in dysthanasia incurred an average cost of 2,316.92 Brazilian Reais (SD = 3,146.60) for tests and procedures in the last 30 days of life. Patients in palliative care had an average cost of 945.40 Brazilian Reais (SD = 2,508.01). There is a statistically significant difference in the invested values between patients in palliative care and those in dysthanasia (U = 620.00; Z = -4.334; p < 0.001). Conclusions: Implementing palliative care can be considered an effective strategy for reducing hospital costs, leading to significant savings within the healthcare system.
Keywords: Cancer; palliative care; end-of-life care; cost analysis